The initiation and arrest stress intensity factors of first year columnar sea ice - Parsons, B. L.; Snellen, J. B.; Muggeridge, D. B. (1988)
Crack growth in ice is slip-stick. Crack growth is initially unstable, for short distances. NRC publication: Yes